Role of School Climate on Types of Self-Regulated Learning (Growth Pathway and Well-being Pathway Types) among Students in Modern Islamic Boarding Schools - Zega, Zulfiah Sumirna; Dadeh, Tarmidi; Nauly, Meutia (Journal of Education Method and Learning Strategy, 2025)
This study explores school climate's role in self-regulated learning (SRL) among students at modern Islamic boarding schools (pesantren) in Medan City. As the number of subjects and study hours increases, students face the challenge of learning independently. The research sample consisted of 350 students from grades 8 and 9 across four modern Islamic boarding schools. Data were collected using a Likert scale measuring SRL and school climate. The SRL data used in this study differ from those in other SRL research, as this study analyzes SRL based on different types of self-regulated learning. This distinction is important because it can help students maximize their learning potential and assist educators in assigning appropriate tasks. The regression analysis results indicate that school climate has a significant effect on the growth pathway type of SRL, contributing 5.2%, as well as on the well-being pathway type, contributing 5.7%. These findings highlight the importance of fostering a positive school climate to support students' independent learning, enabling them to achieve their learning objectives more effectively. This study recommends that Islamic boarding school authorities pay greater attention to aspects of school climate to enhance students' learning, self-development and emotional well-being.